Age-related changes in antigen-specific natural antibodies are influenced by sex - Webster, Sarah E.; Tsuji, Naomi L.; Clemente, Michael J.; Holodick, Nichol E. (Frontiers in Immunology, 2023)
Natural antibody (NAb) derived from CD5+ B-1 cells maintains tissue homeostasis, controls inflammation, aids in establishing long-term protective responses against pathogens, and provides immediate protection from infection. CD5+ B-1 cell NAbs recognize evolutionarily fixed epitopes, such as phosphatidylcholine (PtC), found on bacteria and senescent red blood cells. Anti-PtC antibodies are essential in protection against bacterial sepsis. CD5+ B-1 cell-derived NAbs have a unique germline-like structure that lacks N-additions, a feature critical for providing protection against infection. Previously, we demonstrated the repertoire and germline status of PtC+CD5+ B-1 cell IgM obtained from male mice changes with age depending on the anatomical location of the B-1 cells. More recently, we demonstrated serum antibody from aged female mice maintains protection against pneumococcal infection, whereas serum antibody from male mice does not provide protection. We show that aged female mice have significantly more splenic PtC+CD5+ B-1 cells and more PtC-specific serum IgM than aged male mice. Furthermore, we find both age and biological sex-related repertoire differences when comparing B cell receptor (BCR) sequencing results of PtC+CD5+ B-1 cells. While BCR germline status of PtC+CD5+ B-1 cells from aged male and female mice is similar in the peritoneal cavity, it differs significantly in the spleen, where aged females retain germline configuration and aged males do not. Nucleic acid sensing toll-like receptors are critical in the maintenance of PtC+ B-1 cells; therefore, to begin to understand the mechanism of differences observed between the male and female PtC+CD5+ B-1 cell repertoire, we analyzed levels of cell-free nucleic acids and found increases in aged females. Our results suggest the antigenic milieu differs between aged males and females, leading to differential selection of antigen-specific B-1 cells over time. Further elucidation of how biological sex differences influence the maintenance of B-1 cells within the aging environment will be essential to understand sex and age-related disparities in the susceptibility to bacterial infection and will aid in the development of more effective vaccination and/or therapeutic strategies specific for males and females.